How Executive Functions Are Evaluated in Children and Adolescents with Cerebral Palsy? A Systematic Review - Pereira, Armanda; Lopes, Sílvia; Magalhães, Paula; Sampaio, Adriana; Chaleta, Elisa; Rosário, Pedro (Frontiers in Psychology, 2018)
Aims. The aim of the present study was to examine how executive functions are assessed in children and adolescents with Cerebral Palsy. Method. A systematic literature review was conducted using four bibliographic databases (WebScience, Scopus, PubMed, and Psycinfo), and only studies that evaluated at least one executive function were selected. Both the research and reporting of results were based on Cochrane’s recommendations and PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines. Results. The instrument most frequently used was the D-KEFS. All studies point to the existence of impairments in the executive functions among children and adolescents with Cerebral Palsy with an impact on several cognitive and life domains. Interpretation. There is a need to further systematize the research protocols to study the executive functions and their assessment in the intervention context. Findings of this review presented a diversity of tests (e.g., D-KEFS) or tasks (e.g., The inhibitory ability task) used with children with Cerebral Palsy. However, no information was given about adaptations performed to the test/task to meet Cerebral Palsy’s specificities. Future research could consider including this information, which is key both to researchers and practitioners. The results of this study have important implications and suggestions for future avenues and guidelines for research and practice.